Laser photobiomodulation for chemical stomatitis in intensive care patient: Case report - Lara Rebelo de Almeida; Luciana Ferraz Gominho; Fernando Henrique de Siqueira Cabral; Antônio Carlos Moura de Albuquerque Melo; Lúcia de Fátima Cavalcanti dos Santos; Kaline Romeiro (Sociedade Portuguesa de Estomatologia e Medicina Dentária, 2024)
Chemical stomatitis is a type of traumatic injury caused by contact of chemical substances and drugs with oral tissues, resulting in clinically significant damage. This case reports a 14-year-old male patient with chronic kidney disease on renal replacement therapy (peritoneal dialysis) and using calcium carbonate via oral capsules for treatment. Due to peritoneal dialysis complications, the patient developed bacterial peritonitis, requiring intensive care unit admission and alteration of his dialysis therapy mode to hemodialysis. During the hospitalization period, significant oral lesions developed due to inadequate calcium carbonate administration, interfering with the evolution of the patient's general health and requiring the assistance of a dental team for diagnosis and treatment. The patient was diagnosed with chemical stomatitis. During the clinical examination, ulcerated, bleeding lesions were observed on the lip, jugal mucous membranes, hard palate, and soft palate. Laser photobiomodulation was used as a treatment associated with a topical corticosteroid. Each region received ten 1 J/point, and 60 J of energy were delivered per day/session. In total, 480 J of energy were delivered with a total irradiation time of 4800 s. The patient reported considerable improvement in pain symptoms after the first laser-photobiomodulation session. After 8 sessions, the patient had improved, and laser photobiomodulation proved effective for treating oral lesions.